Perspectives of impaired glucose tolerance management in patients with metabolic syndrome - K. P. Ivanov; V. B. Mychka; Yu. V. Zhernakova; E. V. Tishina; S. N. Tolstov; V. P. Masenko; I. E. Chazova (Кардиоваскулярная терапия и профилактика)
Aim. To assess the effectiveness of vildagliptin, its effects on visceral obesity (VO), carbohydrate and lipid metabolism parameters, and circadian profile (CP) of blood pressure (BP) in patients with metabolic syndrome (MS), Stage I arterial hypertension (AH), and impaired glucose tolerance (IGT). Material and methods. The study included 30 patients, aged 18-60 years (16 men and 14 women). All patients had IGT, VO, and Stage I AH. Previously prescribed antihypertensive therapy (AHT) was not modified after the start of the study. In all participants, carbohydrate and lipid metabolism parameters, BP CP, and body weight were measured at baseline and after 24 weeks of vildagliptin treatment. Results. Vildagliptin therapy was associated with a significant reduction in body weight, waist circumference, postprandial and fasting glucose levels, the levels of total cholesterol and low-density lipoprotein cholesterol, as well as with a sustained reduction in systolic and diastolic BP levels. Conclusion. Vildagliptin therapy resulted in weight reduction, improved carbohydrate and lipid profiles, and target BP achievement, without inducing hypoglycemia episodes.